Intracervical Sperm Deposition and Body Condition Score on the Differences in Conception Rate after First Artificial Cow Insemination - Mirajuddin, Mirajuddin; Padang, Padang; Husain, M. H.; Ismail, Mohammad (Universitas Sebelas Maret, 2025)
Objective: This study specifically aimed to determine the method of sperm deposition during intracervical insemination for the artificial insemination (AI) of Donggala cattle (local cattle from Donggala regency).Methods: This study was conducted in the Donggala regency, Central Sulawesi from July to November 2017. The AI receptor was productive for Donggala cow with a body condition score (BCS) of 2-4. The success of the first AI was determined based on the conception rate (CR).Results: The results showed that the variation in BCS and the intracervical deposition location significantly affected (p <0.05) the CR of the first AI in Donggala cattle. Cows with a BCS of 4 had a higher CR (100%) when compared to a BCS of 3 (76.24%) and a BCS of 2 (74.19%).Conclusions: The sperm deposition location in cervical door IV produced a higher CR rate (95.23%) when compared to III (87.27%), II (75.00%), and I (41.02%). It suggests that the success rate of AI can be increased if the sperm deposition was placed in the cervical door IV and III.